Drug lifecycle control in Sub-Saharan Africa: Book of abstracts to the workshop "Drug lifecycle control in Sub-Saharan Africa - From production to responsible safe disposal and elimination in wastewater treatment plants (Med4Africa)" - Lucie Moeller; Peter Imming; Eliangiringa Kaale (Helmholtz-Zentrum für Umweltforschung (UFZ), 2022)
[Introduction] The circular economy shows the need of observing products in their entire lifecycle - from the production to their fate after the use. Pharmaceuticals are primarily a means of saving lives and ensuring the well-being of people and animals. However, what is the fate of the used pharmaceuticals that are not metabolized and are therefore released into the nature? And, what happens with them if they expire without being used? Is there any possibility to include pharmaceuticals into the circular economy and use the expired drugs as a resource? Would this way be one of the solutions to enhance the resilience of Sub-Saharan Africa in regard to drug shortage due to missing production facilities and their dependency on markets from other continents? To discuss these and more questions in detail from the perspectives of the drug development, production, safe use, responsible disposal, and possible reuse, more than 30 professionals working in universities, government agencies, control laboratories, hospital pharmacies and manufacturing pharmaceutical companies from seven countries (six Sub-Saharan countries - Tanzania, Ethiopia, Botswana, Kenya, Nigeria, and Rwanda - as well as Germany) met in a workshop with the title "Drug lifecycle control in Sub-Saharan Africa - From production to responsible safe disposal and elimination in wastewater treatment plants". The workshop took place in Arusha (Tanzania) in September 2022 and was financed by the Volkswagen Foundation in frame of the initiative "Knowledge for Tomorrow - Cooperative Research Projects in Sub-Saharan Africa". In addition to numerous lectures on topics related to the overarching topic of "Drug Lifecycle Control", there was also a practical part on the use of simple technologies to determine the active ingredient content of drugs. Such technologies also complement the Global Pharma Health Fund (GPHF) Minilab, the use of which was demonstrated on site at the central drug control laboratory in northern Tanzania. A large part of the workshop was devoted to planning which research projects could be specifically addressed from among the participants. This UFZ report involves the abstracts of the talks of the workshop the presentation of which are presented on the website "www.ufz.de/med4africa". The aim of this report is to provide a brief overview of the issues that have been discussed and need to be discussed further in regard to pharmaceuticals in relation to the circular economy in (but also outside of) Sub- Saharan Africa.
Additional information: Date of the workshop: 29 August 2022 - 03 September 2022.
Keywords: 330